Small modular reactors : nuclear power fad or future? - Ingersoll, Daniel T. (Woodhead Publishing in energy., 2016)
There is currently significant interest in the development of small modular reactors (SMRs) for the generation of both electricity and process heat. SMRs offer potential benefits in terms of better affordability and enhanced safety, and can also be sited more flexibly than traditional nuclear plants. Small Modular Reactors: Nuclear Power Fad or Future? reviews SMR features, promises, and problems, also discussing what lies ahead for reactors of this type. The book is organized into three major parts with the first part focused on the role of energy, especially nuclear energy, for global development. It also provides a brief history of SMRs. The second major part presents basic nuclear power plant terminology and then discusses in depth the attributes of SMRs that distinguish them from traditional nuclear plants. The third and final major section discusses the current interest in SMRs from a customer's perspective and delineates several remaining hurdles that must be addressed to achieve wide-spread SMR deployment.